PENJUALAN PT. DCIKA PRIMA MAHKOTA CABANG PINANG RANTI DIPENGARUHI OLEH HARGA MELALUI PROMOSI - Dewi Alyani; Edy Sanusi Silitonga (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2021)
Dcika Prima Mahkota is engaged in Cake & Bakery which is known as D'Cika Cakes & Bakery. We are a growing company, currently we have 13 branches in Jakarta and Bekasi with professional experts in their fields. This study aims to analyze the simultaneous effect of price and promotion on increasing sales, analyzing the partial effect of price on increasing sales and analyzing the partial effect of promotion on increasing sales. The analysis technique uses path analysis and multiple regression. The results of the analysis show that the price and promotion simultaneously have a significant effect on increasing sales, which means that the more affordable the price is and the more attractive the promoted product can increase sales. Price has an effect on increasing sales, this shows that the more affordable the price offered to consumers can increase sales. Promotions are increasingly interested in promotions that can improve purchasing decisions.